The Role of Financial Self-Efficacy in Digital Financial Literacy and Financial Behavior: Evidence from Indonesia - Sinta Putriana; Fadjar Harimurti; Antaresti Dwi Kinanthi (Jurnal RAK (Riset Akuntansi Keuangan), 2025)
This study examines how young people's financial behaviors are impacted by digital financial literacy through financial self-efficacy. The study uses a quantitative, explanatory approach that utilizes PLS-SEM. 268 respondents from Generation Z and Millennials with at least 6 months of experience with digital financial products, such as mobile banking and digital wallets, comprised the final sample for this study. The findings of this study indicate that digital financial literacy positively affects financial self-efficacy, which in turn positively influences financial behavior. Furthermore, digital financial literacy has both direct and indirect effects on financial behavior. This association is somewhat mediated by financial self-efficacy. The results of this study demonstrate that digital financial literacy increases knowledge and skills while fostering financial confidence. This eventually promotes prudent and accountable financial conduct in the digital era. The results suggest that digital financial literacy should be integrated into financial education programs, especially in countries such as Indonesia, where fintech adoption is accelerating.